2022
DOI: 10.1039/d1tb02862f
|View full text |Cite
|
Sign up to set email alerts
|

Legumain-mediated self-assembly of a 131I-labelled agent for targeted radiotherapy of tumors

Abstract: Targeted radionuclide therapy (TRT) has been a promising strategy for cancer therapy, which can inhibit or kill cancer cells by selectively delivering radionuclide to target tissues. Herein, a legumain-targeted therapeutic...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
(43 reference statements)
0
5
0
Order By: Relevance
“…13 Since legumain is an asparaginyl endopeptidase that is overexpressed in tumor cells exhibiting aggressive migration and invasion, 23−26 it is an attractive candidate as a tumor-associated enzyme for enhanced therapy and imaging. 27,28 The exact sequence and chemical structure of all peptides used in this study are shown in Table 1. Successful synthesis of R 1 −R 6 peptides and their Alexa Fluor 488-conjugated counterparts (for the visualization of intracellular internalization) was verified using MALDI-TOF spectrometry (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Since legumain is an asparaginyl endopeptidase that is overexpressed in tumor cells exhibiting aggressive migration and invasion, 23−26 it is an attractive candidate as a tumor-associated enzyme for enhanced therapy and imaging. 27,28 The exact sequence and chemical structure of all peptides used in this study are shown in Table 1. Successful synthesis of R 1 −R 6 peptides and their Alexa Fluor 488-conjugated counterparts (for the visualization of intracellular internalization) was verified using MALDI-TOF spectrometry (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…To align our study with the relevant biological studies, we designed polyarginine peptide sequences with a legumain enzyme recognition motif: alanine–alanine–asparagine (AAN) bound to CK (AANCK), where cysteine facilitates self-assembly into nanostructures and lysine facilitates linkage to imaging probes such as Alexa Fluor 488 (optical probe) or olsalazine (CEST MRI probe) . Since legumain is an asparaginyl endopeptidase that is overexpressed in tumor cells exhibiting aggressive migration and invasion, it is an attractive candidate as a tumor-associated enzyme for enhanced therapy and imaging. , The exact sequence and chemical structure of all peptides used in this study are shown in Table . Successful synthesis of R 1 –R 6 peptides and their Alexa Fluor 488-conjugated counterparts (for the visualization of intracellular internalization) was verified using MALDI-TOF spectrometry (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Then, the medium was removed, and a series of radiation doses of [ 18 F]AlF-RSM (0.23, 0.46, 0.93, 1.85, and 3.7 MBq) in 300 μL of medium were added and incubated for 24 h. Then the cell viability was measured using the MTT method. 36 For the colony formation assay, A549, PC-3, U87, A375 cells (1000 cells/well), and MDA-MB-468 (6000 cells/well) were preseeded into 24-well plates to incubate overnight. Similarly, the cells were further incubated with different radiation doses of [ 18 F]AlF-RSM (0.23, 0.46, 0.93, 1.85, and 3.7 MBq) for 10−14 days.…”
Section: Synthesis Of Nonradioactive Rsm and [ 19 F]alf-rsmmentioning
confidence: 99%
“…For the radioactive toxicity assay, MDA-MB-468, A549, PC-3, U87, and A375 cells were seeded into 96-well plates at a density of 1 × 10 4 cells/well and incubated overnight. Then, the medium was removed, and a series of radiation doses of [ 18 F]­AlF-RSM (0.23, 0.46, 0.93, 1.85, and 3.7 MBq) in 300 μL of medium were added and incubated for 24 h. Then the cell viability was measured using the MTT method . For the colony formation assay, A549, PC-3, U87, A375 cells (1000 cells/well), and MDA-MB-468 (6000 cells/well) were preseeded into 24-well plates to incubate overnight.…”
Section: Experimental Sectionsmentioning
confidence: 99%
“…Hence, we intended to develop a tumor-targeted HCy probe ( HCy-AAN-Bio ) for FL/PA imaging of legumain in vivo. HCy-AAN-Bio consists of three parts: (1) the signal part HCy for activatable FL/PA imaging; (2) the legumain recognition part Ala-Ala-Ala (AAN) for legumain-specific cleavage; , (3) the targeted part biotin for targeting tumors with abundant biotin receptors on the cell surface (Figure ). The aminated amino group of HCy-AAN-Bio prevented intramolecular charge transfer (ICT) from the amino group to the positively charged nitrogen heterocyclic portion, resulting in the disappearance of the FL/PA signal.…”
mentioning
confidence: 99%